New species of Polycentropodidae (Trichoptera: Annulipalpia) from Northeast Region, Brazil - Vilarino, Albane; Calor, Adolfo R. (Zootaxa, 2015)
Three new species of Polycentropodidae (Insecta: Trichoptera) from the Northeast Region of Brazil are diagnosed, described, and illustrated. Polycentropus brevicornutus n. sp. of the Polycentropus gertschi Group can be diagnosed mainly by its much reduced, almost vestigial intermediate appendages, and by the inferior appendages, which are deltoid and very linear in lateral aspect. The two new species of Polyplectropus are P. anchorus n. sp. and P. auriplicatus n. sp. in the P. annulicornis and P. bredini Groups, respectively. Polyplectropus anchorus n. sp. is very similar to P. annulicornis Ulmer 1905, but can be distinguished from its congener mainly by the endothecal spines without setae and with their apices directed dorsolaterad. Polyplectropus auriplicatus n. sp. resembles P. brasilensis but can be distinguished mainly by the shorter and deltoid intermediate appendages, the straighter dorsolateral processes of the preanal appendages, and the inferior appendages each with its mesoventral branch more developed and rounded.